Implementation of Accreditation Management At Madrasah Aliyah Negeri 2 Sumedang - Sariah, Dedeh (Fahmina: Jurnal Pendidikan Islam, 2024)
This research is motivated by the inadequate accreditation preparation time as the main cause of the madrasah unpreparedness in the accreditation assessment process. The head of the madrasah needs to provide special time for teachers and staff to take care of the required documents. In addition, the head of the madrasah must always be ready with information regarding summonses and notifications from the Agency, as well as changes in the accreditation assessment schedule. . This study aims to find out the accreditation management of MAN 2 Sumedang which includes the planning, implementation and evaluation of accreditation. This research uses a qualitative method. This research is located at MAN 2 Sumedang, a flagship madrasah with an accreditation status of "A" and a score of 93 based on the decision of the National Accreditation Board for Madrasahs/Madrasas. The results of the study show that accreditation planning is carried out through deliberations involving all stakeholders and the formation of an accreditation team that collects the necessary documents. The implementation of accreditation was carried out online using Zoom for two days, including questions and answers and learning observations. Accreditation evaluations are conducted after the grades come out, with a focus on identifying deficiencies and continuous improvement. The evaluation aims to measure the program's achievement, generate recommendations, and make decisions for continuous improvement.